Популяризація космології: віхи історії (до 170–річчя Каміля Фламмаріона) - Колтачихіна, О. Ю. (НТУ "ХПІ", 2013)
Стаття присвячена 170–річчю з дня народження маловідомого в україномовній науковій літературі популяризатора та історика космології та астрономії, дослідника–астронома Каміля Фламмаріона. Велику увагу приділено його працям, що стосуються історії та популяризації космології.

The article is devoted to the 170th anniversary of the birth of a little-known in Ukrainian-language scientific literature popularizer and historian of cosmology and astronomy, a French astronomer and author Camille Flammarion. His cosmological works and works of history of cosmology is devoted much attention
Keywords: космологія; історія космології; історія науки; популяризація науки; популяризація космології; cosmology; history of cosmology; history of science; popularize of science; popularize of cosmology